Relationship Between Body Surface Area and Arterial Concentrations of Bupivacaine Following Lumbar Epidural Anesthesia. Issue 2 (March 1995) - Sharrock, Nigel E.; Go, George; Mineo, Robert; Urmey, William F.; Arthur, Richard G.
Abstract : Background and Objectives: Most prior studies have shown no relationship between body mass or body surface area (BSA) and maximum plasma concentration of local anesthetic agent (Cmax) following neural block. Methods: Forty-nine patients, aged 55 or older, undergoing elective total hip arthroplasty, had arterial plasma bupivacaine concentrations measured (gas chromatography) at 10-minute intervals for the first 60 minutes following lumbar epidural injection of 25 mL 0.75% bupivacaine plain. Hemodynamic stability was maintained with either low-dose epinephrine (EPI) or phenylephrine (PHE) intravenous infusions. Results: A significant relationship between arterial bupivacaine concentration and BSA was noted for both EPI and PHE groups at each observation point ( P < .05). In addition, Cmax for each group was correlated to both BSA and body mass ( P < .05). Arterial plasma bupivacaine concentrations were significantly higher in patients at 10, 20, 30, and 40 minutes following epidural injection in patients receiving PHE than EPI ( P < .05). Conclusions: Between 20% and 40% of the variability in the arterial concentrations of bupivacaine following lumbar epidural injection in elderly patients can be accounted for by differences in BSA.